The Hydrosocial and Dwelling Perspectives of Telaga (Pond) in Gunungsewu Karst of Gunungkidul - Martias, Irsyad (Universitas Airlangga, 2024)
Gunungsewu Karst is a representation of a harsh drought region. For generations, local people have relied on telaga (pond), the only karst surface feature that can harvest rainwater, to fulfill their water needs. This anthropological study adopts hydrosocial and dwelling perspectives to understand how local people perceive and respond to ecological changes surrounding telaga over time. Furthermore, it aims to demonstrate that the functions of telaga transcend its material benefits. By exploring myths, water rites (merti telaga), and people's memory, I argue that the telaga serves as a waterscape and cosmological inspiration where humans and nonhumans (in this discussion, trees and water) interact, protect, and provide life to each other. This study also reveals that environmental changes in the telaga strongly stimulate the community to reorganize its cosmological realm. In other words, the accumulation of intersubjective relationships between local communities and the telaga can also be perceived as a historical process that creates a